The effect of the hypohydration on the lactate threshold in a hot and humid environment - Papadopoulos, C.; Doyle, J.; Rupp, J.; Brandon, L.; Benardot, D.; Thompson, W. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The purpose of this study was to investigate the effect of hypohydration (HH) on the lactate threshold (LT) in a hot and humid environment. Methods. Ten apparently healthy males (age 25±3 yrs; height 1.8±0.04 m; mass 78±12 kg; V.O2peak 3.7±0.4 L/min) underwent four randomly assigned maximal treadmill tests. Two trials were at room temperature (22±1 °C; RH=50%) under two different hydration conditions : euhydrated (EH-RM) and hypohydrated (HH-RM), and two trials were performed in a warm chamber (37±0.5 °C; RH=70%) under two different hydration conditions: euhydrated (EH-HT) and hypohydrated (HH-HT). The desired HH level (2-4%) was accomplished in the 24+ hours before testing by fluid restriction. Mean HH was 2.6±1.0% body weight. Capillary blood samples were collected at the end of each stage and analyzed for lactic acid (LA). LA concentrations were plotted for each exercise stage, and the LT was determined by visual inspection as the highest exercise stage at which blood LA concentration began to increase above each individual's resting levels. LT and body temperature were analyzed with a two-way repeated measures ANOVA (P<0.05). Results. During the trials in the warm chamber, the LT occurred at a significantly earlier stage compared to the thermoneutral environment (4.4±0.09 vs 5.8±0.10) and with a significantly lower oxygen consumption (2.38±0.09 L·min-1 vs 2.86±0.13 L·min-1). Body temperature at the LT was significantly higher in the heat trials compared to room temperature (38.7±0.12 °C vs 37.6±0.14 °C). LT determination was not significantly altered by hydration. Conclusion. These results suggest that during progressive incremental maximal treadmill exercise, moderate HH does not affect the LT, whereas exercise in a hot and humid environment induces a downward shift in the LT. The elevated body temperature during the heat trials suggests that body temperature may affect running performance associated with the LT.